(untitled) (Contemporary Mathematics, 2025)
This work rigorously proves the existence of attractors of a finite collection of generalized multivalued mappings which are generalized mapping that are defined in the setup of partial metric spaces. We hereby put forward Generalized Multivalued Iterated Function Systems (GMIFS) and we obtain corresponding results under different types of assumptions known as generalized contractive circumstances. We construct a few examples that can be used to illustrate the results obtained in this manuscript. Additionally, this work extends several outcomes documented in prior studies within the fields of Iterated Function Systems (IFS).